On Sombor Energy of the Nilpotent Graph of the Ring of Integers Modulo ε - Putra, Lalu Riski Wirendra; Albaracin, Jimboy R.; Wardhana, I Gede Adhitya Wisnu (IndoMS, 2025)
In chemical graph theory, chemical compounds are represented as graphs where atoms are represented as vertices, and the bonds connecting the atoms are represented as edges. In 2021, Gowtham and Swamy discovered another type of graph energy, called the Sombor energy. This discovery was motivated by Gutman's introduction of the Sombor index in the same year. In the field of abstract algebra, rings can also be represented as graphs. In this article, we aim to explore the Sombor energy of some nilpotent graphs of rings, particularly the ring of integers modulo ε.